Construção de um fluxograma para identificação e notificação de violência e maus-tratos contra a pessoa idosa - Barreto, Adriana Maria Moreira Alexandre (2019)
Introduction: With the growing aging of the elderly population, it is necessary the look of managers and health professionals who understand their specificities for daily care and promotion of their quality of life. In addition, the aging process associated with socioeconomic difficulties, may be exposed to adversities such os neglect and ill-treatment that generate the violence suffered by this population and constitutes a major problem imperceptible to society. Objectives: Search for evidence in the literature to guide and strengthen the discussion on the violence against the elderly person. Know what health professionals think about the violence and abuse against the elderly person within the hospital. Propose a flowchart to guide health professionals to identify and report cases of violence and abuse against the elderly in the hospital context. Method: Methodological study with mixed (quantitative and qualitative), structured in three stages: integrative literature review; field study and the technological product. Forty-two health professionals from a hospital in a City in the state of Ceará, selected by convenience, participated in the field study, considering the inclusion criteria that agreed to participate in the research. For data collection, a semi- structured interview was used. Data were processed using IRaMuTeQ® software and the categorial thematic content analysis technique. Results: The results revealed four categories: (1) Lack of knowledge about the identification and notification of violence; (2) Understanding the priority of assistance; (3) Recognition of the needs for specific care of elderly people; (4) Knowledge about violence against elderly people by health professionals. Discussion: It was found that the professionals in the hospital environment, even in the presence of cases of violence, can not identify them and, consequently, do not notify them, hence the importance’s for professionals to use an instrument that can guide the identification of cases of violence to notify and refer the competent government agency for the protection of the rights of the elderly available in the county. Final Thoughts: It is observed that the elderly facing violence in different contexts, particulary in the hospital is not yet reported due to lack of preparation. In this sense, was fetched build an instrument based on a flowchart of identification, notification and referral, for elderly people who are victims of violence and abuse, to be used by hospital professionals.